Acumen Message Drop Scheme (AMD) in Opportunistic Networks - Lenando, Halikul; Ali, Aref Hassan K.; Alrfaay, Mohamad (International Journal of Sensors Wireless Communications and Control, 2021)
Background: In traditional networks, nodes drop messages to free up enough space for buffer optimization. However, keeping messages alive until they reach their destination is crucial in Opportunistic Networks. Therefore, this paper proposes an Acumen Message Drop scheme (AMD) that considers the impact of the message drop decision on data dissemination performance. Methods: To achieve this goal, AMD drops the message based on the following considerations: the estimated time of the arrival of the message to its destination, message time to live, message transmission time, and the waiting time of the message in the queue. AMD scheme works as a plug-in in any routing protocol. Results: Performance evaluation shows that the integration of the proposed scheme with the PRoPHET routing protocol may increase efficiency by up to 80%, while if integrated with an Epidemic routing protocol, efficiency increases by up to 35%. Moreover, the proposed system significantly increases performance in the case of networks with limited resources. Conclusion: To the best of our knowledge, most of the previous works did not address the issue of formulating the message drop decision in the non-social stateless opportunistic networks without affecting performance.
Keywords: wireless sensor networks